A 10 YEAR EXPERIENCE OF OVER 100 FRONTOFACIAL PROCEDURES IN SYNDROMIC CHILDREN AND THEIR COMPLICATIONS. (29th November 2012) - Abela, CA; Mclellan, L; Truscott, K; Jeelani, O; Dunaway, D; Britto, J; Hayward, R; Jones, B; Diwan, Z
Abstract : Complex craniofacial procedures form a distinct subgroup of transcranial or frontofacial surgery. The paediatric population undergoing these procedures mainly include the syndromic dysostoses, central facial hypoplasias or clefts and cranio-fronto-nasal dysplasia. We reviewed the case notes, hospital electronic records, logbooks and departmental database to review the series of frontofacial cases over the last 10 years. We collated demographic data, clinical diagnoses, operative records and episodic details. The unit has performed 105 frontofacial surgical procedures in children with Apert, Crouzon, Pfeiffer and other Syndromes. Within this population, it has been necessary to perform monobloc distractions, facial bipartition distractions, box osteotomies and facial bipartitions without distraction, as well as 2 Le Fort 3 advancements in combination with Fronto-orbital remodelling. During this period we have recorded 58 complications. From the patients that were investigated, there was a 9% major complication rate and 4% revision rate. Bipartition and box osteotomy procedures are significantly safer than distraction procedures. Overall, the main findings were as follows: Peri-operative mortality rate 1% Relapse rate 2% Peri-operative massive transfusion risk 5% Post-operative epilepsy for distraction 5% Frontofacial surgery is comparable to other complex major surgeries Distraction increases complication rate and doubles hospital stay but is still safe.